Canadian academic nursing librarians: impacts of the COVID-19 pandemic on librarianship practice. - Miller, Katherine; Janke, Robert (Journal of the Canadian Health Libraries Association (JCHLA), 2022)
Objective: This study explored changes in the practice of academic nursing librarianship at large Canadian universities during the COVID-19 pandemic with a particular focus on academic nursing librarians' work with nursing graduate students and nursing faculty. Methods: Semi-structured interviews were conducted with eleven academic nursing librarians about changes to their librarianship practice during the COVID-19 global pandemic. Interviews were conducted between 20 April and 14 May 2021, discussing experiences during the study period March 2020 to May 2021. Results: Canadian academic nursing librarians experienced (i) the adoption of the completely virtual library ; (ii) changes to the type and prevalence of online instruction ; (iii) the discovery that online consultations work well; (iv) the discovery of the extent to which relationships are valued and intentional; (v) an increase in requests for instruction and co-authorship of knowledge syntheses; and (vi) the benefits and challenges of remote work. Discussion: Experiences were divergent, shaped in part by the institutions' pre-pandemic practices. Additionally, some participants reported no impact of the pandemic on their research, instruction, and collaborations with nursing graduate students and nursing faculty. In particular, institutions already offering online masters programs in nursing reported less significant disruption. The temporary transition to the completely virtual library revealed benefits of online consultations, opportunities for reaching more students through asynchronous learning, the importance of relationships to nursing liaison work, and value of the flexibility to work remotely. Conclusion: The COVID-19 global pandemic continues to evolve. With a return to in-person classes at Canadian universities, there is much to learn from the experiences during the first 18 months ofthe pandemic.